S138 Blood outgrowth endothelial cells isolated from patients with pulmonary arterial hypertension possess less caveolae and reduced cavin-2 expression. (14th November 2013) - Dunmore, BJ; Howard, G; Crosby, A; Nichols, BJ; Morrell, NW
Abstract : Pulmonary arterial hypertension (PAH) is a progressive disease characterised by a marked elevation in pulmonary arterial pressure due to increased muscularisation and obliteration of small pulmonary arteries. The majority of heritable PAH cases are due to mutations in members of the transforming growth factor-β (TGFβ) receptor signalling pathway. Although predominantly associated with mutations in the bone morphogenetic protein type II receptor (BMPR-II) genetic variations causing disease have recently been identified in caveolin-1, the major component of caveolae generation. Caveolae are flask shaped invaginations in the plasma membrane that play an important role in many endothelial cell functions including vesicular trafficking and signalling. Correct caveolae formation in the lung has recently been shown to require serum deprivation protein response (SDPR), also known as cavin-2. Using blood outgrowth endothelial cells (BOECs) isolated from patients with PAH we sought to determine the expression of cavin-2 and caveolae formation. Methods: Blood outgrowth endothelial cells (BOECs) were isolated from control subjects and individuals with PAH, including BMPR-II mutation and idiopathic patients. Following transmission electron microscopy (TEM) the number of caveolae and depth of invaginations were assessed in ten cells from each cell line. Protein expression of caveolin-1, cavin-1 and cavin-2 were assessed by western blotting. Caveolin-1 and cavin-2 knockout mice were assessed for right ventricular systolic pressure (RVSP) and right ventricular hypertrophy. Results: Reduced caveolae and depth of invaginations were observed in idiopathic PAH patients and individuals with a BMPR-II mutation when compared to controls. Interestingly, an individual with a BMPR-II mutation without disease had similar levels to controls. Furthermore, cavin-2 protein expression was decreased in cells from individuals with pulmonary hypertension, but other caveolae components appeared unaffected. In the absence of a disease stimulus caveolin-1 and cavin-2 knockout mice did not develop pulmonary hypertension although slightly elevated RVSP was observed. Conclusions: Our preliminary data suggests that caveolae formation is dysregulated in cells from individuals with pulmonary hypertension. In addition, reduced levels of cavin-2 could play a significant role in the decreased number of caveolae. Cavin-2 and caveolae generation could therefore be novel therapeutic targets for pulmonary hypertension.